Adhesive Film
A crosslinked acrylic polymer-based adhesive layer with specific monomers and crosslinking agents addresses the issues of reduced adhesive strength and corrosiveness in thin films, providing high adhesion and durability without additional surface treatments.
Patent Information
- Application Number
- JP2023144830
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2032-12-17
AI Technical Summary
Conventional adhesive films with reduced thickness suffer from decreased adhesive strength and require additional surface treatments like corona treatment to enhance adhesion, and they are corrosive to materials like ITO surfaces.
A pressure-sensitive adhesive layer formed by crosslinking an acrylic polymer with specific monomers and a crosslinking agent, such as tolylene diisocyanate or xylylene diisocyanate, to create a thin film with high adhesive strength and adhesion performance without using carboxyl group-containing monomers.
The adhesive layer achieves high adhesive strength and adhesion performance despite being thin, with a thickness of 1 μm to 20 μm, and maintains durability and non-corrosiveness to ITO surfaces.
Smart Images

Figure 0007606573000001 
Figure 0007606573000002 
Figure 0007606573000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive layer that has high adhesive strength and high adhesion properties despite being a thin film having a thickness of 1 μm to 20 μm and is used for bonding between layers of optical components, and to a pressure-sensitive adhesive film using the same. [Background technology]
[0002] 2. Description of the Related Art Various pressure-sensitive adhesive films have been proposed for bonding optical members such as polarizing plates and retardation plates to adherends such as liquid crystal cells via pressure-sensitive adhesive layers (see, for example, Patent Documents 1 and 2). Patent Document 1 describes an optical pressure-sensitive adhesive composition that contains butyl acrylate or the like as a main monomer component and also contains an acrylamide compound or the like. Patent Document 2 describes an optical pressure-sensitive adhesive composition that contains a (meth)acrylate having an alkyl group with 4 to 8 carbon atoms as a main component monomer, a carboxyl group-containing monomer, and a nitrogen-containing vinyl monomer. Furthermore, various pressure-sensitive adhesive films have been proposed that have been devised to increase the refractive index of the pressure-sensitive adhesive layer (see, for example, Patent Documents 3 to 8). Patent Document 3 describes an optical pressure-sensitive adhesive composition that contains a tackifier having an aromatic ring and a refractive index of 1.51 to 1.75. Patent Document 4 describes a pressure-sensitive adhesive sheet containing a pressure-sensitive adhesive composition that contains a copolymerizable polymer of an acrylic acid-modified monomer that contains an aromatic ring. Patent Document 5 describes an optical pressure-sensitive adhesive composition containing a tackifier resin having an aromatic ring and an aromatic phosphate ester plasticizer. Patent Document 6 describes a pressure-sensitive adhesive obtained by curing a pressure-sensitive adhesive composition that contains an acrylic resin and an aromatic compound having one ethylenically unsaturated group. Patent Document 7 describes an optical component in which a retardation film and a birefringent plate are fixed to each other via an acrylic adhesive containing an aromatic monomer. Patent Document 8 describes a pressure-sensitive adhesive composition containing a urethane resin obtained by reacting an aromatic diisocyanate with an aromatic polyester diol. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-177022 A [Patent Document 2] JP 2012-201734 A [Patent Document 3] JP 2007-084762 A [Patent Document 4] JP 2011-153169 A [Patent Document 5] JP 2012-167188 A [Patent Document 6] JP 2012-021148 A [Patent Document 7] JP 2006-293281 A [Patent Document 8] JP 2009-091522 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been a demand for adhesive films used to bond layers of optical components together, with the adhesive layer having a thickness of 20 μm or less in order to facilitate the thinning of optical components. Generally, the adhesive strength of a pressure-sensitive adhesive layer is approximately proportional to the thickness of the pressure-sensitive adhesive layer, and therefore, when the thickness of the pressure-sensitive adhesive layer is reduced, the adhesive strength decreases accordingly.
[0005] However, in recent years, adhesive films have been required to have adhesive strength equivalent to that of conventional adhesive films (with thick adhesive layers of approximately 30 μm) even when the thickness of the adhesive layer is reduced, and also to have durability equivalent to or greater than that of conventional adhesive films when left in high temperature and high humidity environments for long periods of time. Furthermore, because it is possible to make the adhesive layer thinner and to form an adhesive layer that does not require aging treatment (curing at a constant temperature), there is a demand for an NCF (Non Carrier Film) configuration consisting of only the adhesive layer, omitting the adhesive film substrate, and having a component structure of "release film / adhesive layer / release film."
[0006] Furthermore, in conventional pressure-sensitive adhesive films, an aging treatment is carried out after the pressure-sensitive adhesive film is attached to an adherend, which makes it possible to improve the adhesion between the adherend and the pressure-sensitive adhesive layer. However, in the case of NCF-type PSA films, the adhesive layer has already been aged, so the adhesive strength between the adherend and the adhesive layer is insufficient, and therefore there is a problem in that the surface of the adherend needs to be subjected to a surface treatment such as a corona treatment. What is needed is a self-adhesive film that overcomes these requirements and problems.
[0007] In addition, in conventional adhesive films, when the thickness of the adhesive layer is made thin and is 20 μm or less, the adhesive strength inevitably decreases, so that in order to increase the adhesive strength of the adhesive layer, it has been necessary to copolymerize a carboxyl group-containing monomer and its copolymer to produce an adhesive composition and an adhesive layer with improved cohesive strength. However, even if the adhesive layer with increased adhesive strength by copolymerizing a carboxyl group-containing monomer and its copolymer can be made thin and is 20 μm or less in thickness, it has corrosive properties due to the carboxyl group, so it cannot be attached to an adherend that is affected by corrosive properties, such as the ITO surface of a transparent conductive film using ITO. As a result of intensive investigation of these problems, the present inventors have succeeded in obtaining a highly adhesive adhesive layer even when the adhesive layer is made thin, having a thickness of 20 μm or less, without using a carboxyl group-containing monomer or its copolymer.
[0008] The present invention has been made in consideration of the above circumstances, and has an objective of providing an adhesive layer that has high adhesive strength and high adhesion properties despite being a thin film having a thickness of 1 μm to 20 μm, and an adhesive film using the same. [Means for solving the problem]
[0009] In order to solve the above problems, the technical idea of the present invention is to provide an adhesive layer formed by crosslinking an adhesive composition made of an acrylic polymer, in which at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14 is used as a main monomer, and at least one copolymerizable nitrogen-containing vinyl monomer is contained as another copolymerizable monomer, and the monomers are copolymerized and crosslinked to provide an adhesive layer having strong adhesive strength and high adhesion properties.
[0010] Further, in order to solve the above-mentioned problems, the present invention provides a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and (D) a crosslinking agent selected from a polyisocyanate compound of tolylene diisocyanate and a polyisocyanate compound of xylylene diisocyanate, the acrylic polymer being a copolymer obtained by copolymerizing a total of 100 parts by weight of at least two or more types selected from the group of compounds consisting of (A) alkyl (meth)acrylate monomers having an alkyl group carbon number of C1 to C14 and (meth)acrylate monomers containing an aromatic group, (B) 5 to 20 parts by weight of one or more types of nitrogen-containing vinyl monomers not containing a hydroxyl group and a carboxyl group, and (C) 0.1 to 5 parts by weight of at least one or more types of copolymerizable vinyl monomers containing a hydroxyl group, without containing a copolymerizable vinyl monomer containing a carboxyl group, the (C) hydroxyl group-containing copolymerizable vinyl monomer being selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxyoctyl (meth)acrylate, 5-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxyoctyl (meth)acrylate, 5-hydroxyoctyl (meth)acrylate, 6-hydroxyoct ...5-hydroxyoctyl (meth)acrylate, 5-hydroxyoctyl (meth)acrylate, 5-hydroxyoctyl (meth)acrylate, and (A) at least one compound selected from the group consisting of alkyl (meth)acrylate monomers having an alkyl group carbon number of C1 to C14 and (meth)acrylate monomers containing an aromatic group, the adhesive layer having a thickness of 1 μm to 20 μm and an adhesive strength of 4.0 to 5.0 μm.The present invention provides a pressure-sensitive adhesive layer having a crosslinking strength of 0.01 to 5 parts by weight, and characterized in that the pressure-sensitive adhesive composition contains 0.01 to 5 parts by weight of the (D) crosslinking agent per 100 parts by weight in total of at least two or more types selected from the group consisting of (A) alkyl (meth)acrylate monomers having a carbon number of C1 to C14 in the alkyl group and (meth)acrylate monomers containing an aromatic group.
[0011] In addition, it is preferable that the adhesive strength when the thickness of the adhesive layer is 5 μm is 4.0 (N / 25 mm) or more.
[0012] The pressure-sensitive adhesive composition preferably contains (A) 100 parts by weight of a main component (meth)acrylate monomer comprising at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14, (B) 5 to 50 parts by weight of one or more nitrogen-containing vinyl monomers, (C) 0.1 to 5 parts by weight of at least one copolymerizable vinyl monomer containing a hydroxyl group, and a copolymer having a weight average molecular weight of 200,000 to 2,000,000, and (D) 0.01 to 5 parts by weight of a crosslinking agent.
[0013] The pressure-sensitive adhesive layer preferably has a refractive index of 1.47 to 1.50.
[0014] The present invention also provides a pressure-sensitive adhesive film, characterized in that the pressure-sensitive adhesive layer is formed on one side of a release film, and has a structure of release film / pressure-sensitive adhesive layer / release film.
[0015] The present invention also provides a pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer laminated on one surface of a substrate.
[0016] The present invention also provides a film for peripheral members of polarizing plates, which uses the pressure-sensitive adhesive film.
[0017] The present invention also provides a film for a touch panel, which uses the pressure-sensitive adhesive film.
[0018] The present invention also provides a film for electronic paper, which uses the pressure-sensitive adhesive film.
[0019] The present invention also provides a film for organic electroluminescence (EL) display, which uses the pressure-sensitive adhesive film.
[0020] The present invention also provides a pressure-sensitive adhesive layer-attached optical film comprising an optical film and the pressure-sensitive adhesive layer laminated on at least one surface of the optical film. Effect of the Invention
[0021] According to the present invention, it is possible to overcome the conventional requirements and problems and provide an adhesive layer having high adhesive strength and high adhesion performance despite being a thin film having a thickness of 1 μm to 20 μm, and an adhesive film using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described below based on preferred embodiments. The pressure-sensitive adhesive layer of the present invention is characterized in that, in the pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition made of an acrylic polymer, the pressure-sensitive adhesive layer has a thickness of 1 μm to 20 μm and an adhesive strength of 4.0 (N / 25 mm) or more when the thickness is 5 μm.
[0023] The pressure-sensitive adhesive composition according to the present invention preferably contains, as the main component (meth)acrylate monomer, at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14. Examples of the alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14 include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, cyclopentyl (meth)acrylate, and cyclohexyl (meth)acrylate. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched or cyclic. The proportion of the (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C14 is preferably 50 to 95 parts by weight per 100 parts by weight of the acrylic polymer (copolymer) in the pressure-sensitive adhesive composition. Furthermore, in the adhesive layer of the present invention, the adhesive composition contains 20 parts by weight or more of methyl acrylate monomer out of 100 parts by weight of (meth)acrylate monomer as the main component, which is one or more alkyl (meth)acrylate monomers having an alkyl group with a carbon number of C1 to C14, thereby making it possible to increase the refractive index of the adhesive layer to 1.47 or more.
[0024] The adhesive composition according to the present invention may further contain one or more aromatic group-containing (meth)acrylate monomers as the main component (meth)acrylate monomer. Examples of aromatic group-containing (meth)acrylate monomers include benzyl (meth)acrylate, naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxybutyl (meth)acrylate, 2-(1-naphthyloxy)ethyl (meth)acrylate, 2-(2-naphthyloxy)ethyl (meth)acrylate, 6-(1-naphthyloxy)hexyl (meth)acrylate, 6-(2-naphthyloxy)hexyl (meth)acrylate, 8-(1-naphthyloxy)octyl (meth)acrylate, and 8-(2-naphthyloxy)octyl (meth)acrylate. In order to obtain an adhesive layer with a high refractive index, it is preferable to blend at least one aromatic group-containing (meth)acrylate monomer.
[0025] By mixing these aromatic group-containing (meth)acrylate monomers with the main monomer alkyl (meth)acrylate monomer having a carbon number of C1 to C14 in the alkyl group, the refractive index of the obtained pressure-sensitive adhesive layer can be increased and adjusted, and the refractive index difference between optical members can be reduced to reduce total reflection, thereby improving the total light transmittance. In the pressure-sensitive adhesive layer according to the present invention, when the aromatic group-containing (meth)acrylate monomer is contained in the pressure-sensitive adhesive composition, it is preferable to contain it in a ratio of 5 to 30 parts by weight per 100 parts by weight of the main (meth)acrylate monomer. In addition, by copolymerizing a (meth)acrylate monomer containing an aromatic group, the refractive index of the adhesive layer can be increased even further than the effect of increasing the refractive index of the adhesive layer by including 20 parts by weight or more of methyl acrylate monomer among 100 parts by weight of the above-mentioned main component (meth)acrylate monomer. As described above, there are two methods for increasing the refractive index of the adhesive layer: a method in which 20 parts by weight or more of methyl acrylate monomer is included in 100 parts by weight of the main component (meth)acrylate monomer, and a method in which a (meth)acrylate monomer containing an aromatic group is copolymerized. Although each method can be used alone, it is more preferable to use the two methods in combination.
[0026] The pressure-sensitive adhesive composition according to the present invention preferably contains at least one nitrogen-containing vinyl monomer as another copolymerizable monomer. Examples of the nitrogen-containing vinyl monomer include cyclic nitrogen vinyl compounds such as N-vinylpyrrolidone, N-vinylcaprolactam, and (meth)acryloylmorpholine; dialkyl-substituted (meth)acrylamides such as N-ethyl-N-methyl(meth)acrylamide, N-methyl-N-propyl(meth)acrylamide, N-methyl-N-isopropyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-dibutyl(meth)acrylamide; N-ethyl-N-methylaminoethyl(meth)acrylate, N-methyl-N-propylaminoethyl(meth)acrylate, N-methyl-N-isopropylaminoethyl(meth)acrylate, N,N-dimethylaminomethyl(meth)acrylate, and N,N-dimethylaminoethyl(meth)acrylamide; acrylate, dialkylamino(meth)acrylates such as N,N-dimethylaminopropyl(meth)acrylate, N,N-dimethylaminobutyl(meth)acrylate, N,N-dipropylaminoethyl(meth)acrylate, and N,N-dibutylaminoethyl(meth)acrylate; dialkyl-substituted aminoalkyl(meth)acrylamides such as N-ethyl-N-methylaminopropyl(meth)acrylamide, N-methyl-N-propylaminopropyl(meth)acrylamide, N-methyl-N-isopropylaminopropyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, N,N-dipropylaminopropyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylamide, and N,N-diethylaminoethyl(meth)acrylamide, and the like.
[0027] The nitrogen-containing vinyl monomer is preferably one that does not contain a hydroxyl group, more preferably one that does not contain a hydroxyl group or a carboxyl group, so as to be distinguishable from the compound (C) described later.As such a monomer, the monomers exemplified above, for example, acrylic monomers containing N,N-dialkyl-substituted amino groups or N,N-dialkyl-substituted amide groups; N-vinyl-substituted lactams such as N-vinylpyrrolidone and N-vinylcaprolactam; and N-(meth)acryloyl-substituted cyclic amines such as N-(meth)acryloylmorpholine are preferred.
[0028] In the pressure-sensitive adhesive layer according to the present invention, the nitrogen-containing vinyl monomer contained in the pressure-sensitive adhesive composition can impart the necessary adhesive strength and durability to the pressure-sensitive adhesive layer. In the pressure-sensitive adhesive layer according to the present invention, the nitrogen-containing vinyl monomer contained in the pressure-sensitive adhesive composition is preferably 5 to 50 parts by weight per 100 parts by weight of the (meth)acrylate monomer as the main component. In the pressure-sensitive adhesive layer according to the present invention, examples of the nitrogen-containing vinyl monomer contained in the pressure-sensitive adhesive composition that can be particularly preferably used include N-vinylpyrrolidone, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-dibutyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylamide, and N-vinylcaprolactam.
[0029] The pressure-sensitive adhesive composition according to the present invention preferably further contains, as the other copolymerizable monomer, at least one copolymerizable vinyl monomer containing a hydroxyl group. Examples of copolymerizable vinyl monomers containing a hydroxyl group (hydroxyl group-containing monomers) include at least one of hydroxyalkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and hydroxyethyl (meth)acrylate; and hydroxyl group-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. In addition, in the pressure-sensitive adhesive layer according to the present invention, the hydroxyl group-containing monomer contained in the pressure-sensitive adhesive composition can be used as a copolymerizable monomer for reducing the content of the carboxyl group-containing monomer, which is believed to affect the corrosiveness of the resulting pressure-sensitive adhesive layer against a corrodible adherend such as the ITO surface of a transparent conductive film. Therefore, the hydroxyl group-containing monomer can be used to improve the adhesive strength of the pressure-sensitive adhesive layer and reduce the corrosiveness. In the pressure-sensitive adhesive layer according to the present invention, the hydroxyl group-containing monomer contained in the pressure-sensitive adhesive composition is preferably 0.1 to 5 parts by weight per 100 parts by weight of the (meth)acrylate monomer, which is the main component.
[0030] The copolymer of the pressure-sensitive adhesive composition used in the pressure-sensitive adhesive layer of the present invention preferably contains 100 parts by weight of (A) a main component (meth)acrylate monomer comprising at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14, 5 to 50 parts by weight of (B) one or more nitrogen-containing vinyl monomers, and 0.1 to 5 parts by weight of (C) at least one copolymerizable vinyl monomer containing a hydroxyl group. The pressure-sensitive adhesive composition used in the present invention may further contain one or more vinyl monomers containing an aromatic group. The vinyl monomer containing an aromatic group is a monomer containing an aromatic group in its structure, and examples thereof include (meth)acrylate monomers such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate, as well as styrene and α-methylstyrene. By copolymerizing these vinyl monomers containing an aromatic group, the refractive index of the pressure-sensitive adhesive layer formed can be increased and adjusted, and the refractive index difference between optical members can be reduced, thereby reducing total reflection and improving the total light transmittance. When using a vinyl monomer containing an aromatic group, it is preferable to include it in a ratio of 5 to 30 parts by weight out of 100 parts by weight of the (meth)acrylate monomer, which is the main component.
[0031] The polymerization method for the copolymer is not particularly limited, and any known polymerization method can be used as appropriate, such as solution polymerization, emulsion polymerization, etc. The weight average molecular weight of the copolymer is preferably 200,000 to 2,000,000. The copolymer is preferably an acrylic polymer, and preferably contains 50 to 100% by weight of an acrylic monomer such as a (meth)acrylic acid ester monomer, (meth)acrylic acid, or a (meth)acrylamide.
[0032] The properties of the pressure-sensitive adhesive composition, such as required physical properties, can be adjusted by blending the copolymer with a crosslinking agent and / or any suitable additives. Examples of the crosslinking agent include at least one of biuret modified or isocyanurate modified diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, etc., polyisocyanate compounds such as adducts with trivalent or higher polyols such as trimethylolpropane or glycerin, metal chelate compounds, epoxy compounds, etc. The adhesive may also be crosslinked by photocrosslinking using ultraviolet light or the like. When the copolymer is crosslinked using a crosslinking agent, it is preferable that the copolymer has a functional group capable of crosslinking with the crosslinking agent (e.g., a hydroxyl group or a carboxyl group, depending on the type of crosslinking agent), and it is preferable that the copolymer contains a monomer having such a functional group in a side chain. It is also preferable that the pressure-sensitive adhesive composition contains 0.01 to 5 parts by weight of the (D) crosslinking agent. The weight parts are the same as those of (A) to (C) in the copolymer.
[0033] As other optional components, known additives such as silane coupling agents, antioxidants, surfactants, curing accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, curing retarders, processing aids, and antiaging agents can be appropriately blended. These may be used alone or in combination of two or more kinds.
[0034] The pressure-sensitive adhesive layer of the present invention can be obtained by applying the pressure-sensitive adhesive composition to a substrate or a release film, and then crosslinking the pressure-sensitive adhesive composition. When used for bonding between layers of optical components, a thin adhesive layer is desirable, and the thickness of the adhesive layer is preferably 1 μm to 20 μm. Generally, the adhesive strength of an adhesive layer is approximately proportional to the thickness of the adhesive layer, and the adhesive strength when the thickness is 5 μm is preferably 4.0 (N / 25 mm) or more. When the thickness of the adhesive layer is not 5 μm, the "adhesive strength when the thickness is 5 μm" (N / 25 mm) can be estimated by the formula "(adhesive strength when the thickness is 5 μm) = 5F / T", where T (μm) is the thickness of the adhesive layer and F (N / 25 mm) is the adhesive strength of the adhesive layer.
[0035] When the pressure-sensitive adhesive layer according to the present invention is used for bonding between layers of optical members, it is desirable that the difference in refractive index between the pressure-sensitive adhesive layer and the optical member is as small as possible in order to reduce the reflection of light at the interface between the pressure-sensitive adhesive layer and the optical member. For this reason, the refractive index of the pressure-sensitive adhesive layer is preferably 1.47 to 1.50.
[0036] The pressure-sensitive adhesive film of the present invention can be produced by forming the pressure-sensitive adhesive layer of the present invention on one side of a substrate or a release film. As the base film used for forming the pressure-sensitive adhesive layer and the release film (separator) for protecting the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or the like, or an antistatic treatment by coating or kneading an antistatic agent, on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed.
[0037] The surface of the release film that faces the adhesive surface of the adhesive layer is subjected to a release treatment using a silicone-based or fluorine-based release agent. A "release film / adhesive layer / release film" configuration can be achieved by combining the release-treated surfaces of a release film on both sides of a single adhesive layer. In this case, the release films on both sides are peeled off sequentially or simultaneously to expose the adhesive surface, making it possible to attach it to an optical component such as an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films.
[0038] The adhesive film of the present invention can be used to bond various optical films for peripheral components of liquid crystal display devices, mainly polarizing plates, various optical films for touch panels, various optical films for electronic paper, various optical films for organic electroluminescence (EL) displays, and the like. In addition, the pressure-sensitive adhesive layer may be laminated on at least one surface of these optical films to form an optical film with a pressure-sensitive adhesive layer.Specific examples of the optical film include structures such as "optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / release film", "optical film / pressure-sensitive adhesive layer", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film", and "release film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film". For example, in the case of "optical film / adhesive layer / release film" having an adhesive layer protected by a release film, the release film can be peeled off to expose the adhesive layer as in "optical film / adhesive layer", and then laminated with another optical film, thereby obtaining a configuration such as "optical film / adhesive layer / optical film" in which the adhesive layer is used for interlayer bonding. EXAMPLES
[0039] The present invention will now be described in detail with reference to examples.
[0040] <Production of Acrylic Copolymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 60 parts by weight of butyl acrylate, 40 parts by weight of methyl acrylate, 10 parts by weight of N-methylpyrrolidone, 2.0 parts by weight of 6-hydroxyhexyl acrylate, and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic copolymer solution 1 used in Example 1 with a weight average molecular weight of 500,000. A part of the acrylic copolymer was collected and used as a sample for measuring the acid value described later. [Examples 2 to 6 and Comparative Examples 1 to 3] The acrylic copolymer solutions used in Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the acrylic copolymer solution 1 used in Example 1, except that the monomer compositions were as shown in (A), (B), (C), and (C') in Table 1. Although no particular measurement results are shown, the weight average molecular weights of the copolymers contained in the acrylic copolymer solutions of Examples 2 to 6 and Comparative Examples 1 to 3 were in the range of 200,000 to 2,000,000.
[0041] <Production of Pressure-Sensitive Adhesive Composition, Pressure-Sensitive Adhesive Layer, and Pressure-Sensitive Adhesive Film> [Example 1] To the acrylic copolymer solution 1 of Example 1 produced as described above, 0.5 parts by weight of Coronate L-45 (an adduct of a tolylene diisocyanate (TDI) compound) was added and stirred to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film made of a silicone resin-coated polyethylene terephthalate (PET) film, and then dried at 90°C to remove the solvent. The adhesive composition was then aged for 7 days in an atmosphere of 23°C and 50% RH to obtain an adhesive film of Example 1 having an adhesive layer formed by crosslinking the adhesive composition on one side of the release film. [Examples 2 to 6 and Comparative Examples 1 to 3] PSA films of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the PSA film of Example 1 above, except that the compositions of the additives were as shown in Table 1 (D).
[0042] [Table 1]
[0043] In Table 1, the addition ratios of groups (B) through (D) are shown in parts by weight enclosed in parentheses, with the total of group (A) being 100 parts by weight. The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) L-45 and Coronate HL are product names of Nippon Polyurethane Industry Co., Ltd., and D-110N is a product name of Mitsui Chemicals, Inc. TDI means tolylene diisocyanate, XDI means xylylene diisocyanate, and HDI means hexamethylene diisocyanate.
[0044] [Table 2]
[0045] <Test methods and evaluation> The release film (silicone resin-coated PET film) was peeled off from the pressure-sensitive adhesive film in Examples 1 to 6 and Comparative Examples 1 to 3 to expose the pressure-sensitive adhesive layer, which was then transferred to one side of a polarizing plate (film).
[0046] <Method of measuring adhesive strength> An adhesive layer was transferred onto one surface of a polarizing plate (film) having a thickness of 180 μm to obtain an adhesive film (optical film with an adhesive layer) as a sample. The adhesive film was laminated with a pressure roll to the non-tin surface of soda lime glass that had been cleaned with acetone, and then autoclaved at 50°C, 0.5 MPa for 20 minutes. After that, the adhesive was returned to an atmosphere of 23°C and 50% RH. After 1 hour, the peel strength of the adhesive film was measured using a tensile tester in accordance with JIS Z0237 "Test method for adhesive tapes and adhesive sheets." The peel strength when peeled in a 180° direction at a speed of 300 mm / min was taken as the adhesive strength of the adhesive layer of the adhesive film.
[0047] <Adhesion test method> After measuring the adhesive strength, the adhesive layer of the adhesive film sample was visually inspected, and the adhesion was judged based on the state in which the base layer fell off from the polarizing plate (film). ◯: None of the adhesive layer fell off from the base layer. △: Part of the adhesive layer has lifted off from the base layer and fallen off. × The adhesive layer has fallen off from the base layer and transferred to the glass substrate.
[0048] <Durability test method> A 10 cm square adhesive film prepared in the same manner as in measuring the adhesive strength was attached to the non-tin side of soda-lime glass in the same manner to create a sample.The sample was then left in an atmosphere of 60°C and 90% RH for 250 hours, then removed from the sample and placed in an atmosphere of 23°C and 50% RH. After 1 hour, the condition of the adhesive film was visually observed to determine its durability. ○ The adhesive film does not peel off or foam at all. △: Peeling and bubbling have occurred in some parts of the adhesive film. ×··The entire adhesive film has peeling and foaming.
[0049] <Method for Measuring Refractive Index> Measure the refractive index of the adhesive layer at 23°C with an Abbe refractometer (manufacturer: ERMA, model: ER-2S).
[0050] <ITO Corrosion Test> Attach the adhesive layer to the surface of the ITO film, leave it in an atmosphere of 85°C and 90% RH for 1000 hours, and then measure the surface resistance of the ITO film. Taking the surface resistance value of the ITO film before lamination as the initial value, calculate the change rate of the surface resistance. ○··The change rate of the surface resistance is less than 2%. △··The change rate of the surface resistance is 2% or more and less than 5%. ×··The change rate of the surface resistance is 5% or more.
[0051] Table 3 shows the evaluation results.
[0052]
Table 3
[0053] The adhesive films of Examples 1 to 6 had an adhesive strength of the adhesive layer with a thickness of 5 μm of 4.0 N / 25 mm or more, and the refractive index of the adhesive layer was in the range of 1.47 to 1.50, and also had excellent adhesion and durability. That is, with the adhesive films of Examples 1 to 6, the requirements and problems could be overcome.
[0054] The adhesive film of Comparative Example 1 had a weak adhesive strength of the adhesive layer with a thickness of 5 μm, probably because the adhesive composition did not contain a nitrogen-containing monomer. Also, the refractive index of the adhesive layer was low, and it was inferior in adhesion and durability. Further, because the adhesive composition contained a copolymerizable vinyl monomer containing a carboxyl group, it was slightly inferior in ITO corrosion resistance. The adhesive film of Comparative Example 2 had a weak adhesive strength of a 5 μm thick adhesive layer and was slightly inferior in ITO corrosion resistance, probably because the amount of copolymerizable vinyl monomer containing a carboxyl group in the adhesive composition was too large. In addition, the refractive index of the adhesive layer was low, and the adhesion and durability were also slightly inferior. The adhesive film of Comparative Example 3 had a weak adhesive strength of a 5 μm thick adhesive layer, possibly due to the fact that the amount of the hydroxyl group-containing copolymerizable vinyl monomer in the adhesive composition was too high. In addition, the refractive index of the adhesive layer was low, and the adhesive strength was somewhat poor, and the durability was also poor. As described above, the pressure-sensitive adhesive films of Comparative Examples 1 to 3 were unable to overcome the conventional requirements and problems.
Claims
1. A pressure-sensitive adhesive film having a pressure-sensitive adhesive layer formed by crosslinking a pressure-sensitive adhesive composition comprising an acrylic polymer on one side of a substrate, The acrylic polymer is (A) 100 parts by weight in total of at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14; (B) 5 to 50 parts by weight of one or more nitrogen-containing vinyl monomers; (C) a copolymer obtained by copolymerizing 0.1 to 5 parts by weight of at least one copolymerizable vinyl monomer containing a hydroxyl group without containing a copolymerizable vinyl monomer containing a carboxyl group (excluding copolymers containing an ethylenically unsaturated group-containing morpholine compound unit), the (C) hydroxyl group-containing copolymerizable vinyl monomer is at least one compound selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide, and also contains at least one compound selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; The acrylic polymer is a copolymer having a weight average molecular weight of 200,000 to 2,000,000, The thickness of the pressure-sensitive adhesive layer is 1 μm to 20 μm, and the adhesive strength at a thickness of 5 μm is 4.0 (N / 25 mm) or more; The pressure-sensitive adhesive layer has a refractive index of 1.47 to 1.
50. An adhesive film characterized by:
Citation Information
Patent Citations
Double-sided adhesive tape or sheet and method for producing them
JP2005105212A
Optical component and projector
JP2006293281A
Adhesive composition for optics, adhesive layer for optics, optical member with adhesive layer, method for producing the same and image display device
JP2007084762A
Double-sided adhesive sheet
JP2009062486A
Adhesive composition and laminate obtained by using the same
JP2009091522A
